Muir-Torre Syndrome: case report and molecular characterization - Rios, Carolina Alejandra; Villalón, Ricardo; Muñoz, Jorge; Acuña, Mónica; Cifuentes, Lucía (São Paulo Medical Journal, 2014)
CONTEXT: Muir-Torre syndrome is a rare autosomal dominant genodermatosis caused by mutations in the mismatch repair genes. It is characterized by the presence of sebaceous skin tumors and internal malignancies, affecting mainly the colon, rectum and urogenital tract. Awareness of this syndrome among physicians can lead to early diagnosis of these malignancies and a better prognosis. CASE REPORT: We report the case of a Chilean patient who, over the course of several years, had multiple skin lesions, endometrial cancer and colon cancer. The syndrome was diagnosed using molecular techniques such as microsatellite instability analysis, immunohistochemistry and DNA sequencing, which allowed us to find the causative mutation. CONCLUSION: Molecular diagnostics is a highly useful tool, since it allows clinicians to confirm the presence of mutations causing Muir-Torre syndrome. It is complementary to the analysis of the clinical data, such as dermatological presentation, presence of visceral malignancies and family history of colorectal tumors, and it provides important knowledge to help physicians and patients choose between treatment options.